2020
DOI: 10.1186/s12906-020-03147-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of Acacia nilotica (L.) Delile bark fractions against Oral Bacteria, Glucosyltransferase and as antioxidant

Abstract: Background Dental caries and periodontal disease are the most common chronic infectious oral diseases in the world. Acacia nilotica was commonly known in Sudan as Garad or Sunt has a wide range of medicinal uses. In the present study, antibacterial activity of oral bacteria (Streptococcus sobrinus and Porphyromonas gingivalis), inhibitory activity against glucosyltransferase (GTF) enzyme and antioxidant activity were assayed for methanolic crude extract of A. nilotica bark and its fractions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
(50 reference statements)
0
7
2
Order By: Relevance
“…We evaluated the ability of ANPP to scavenge hydroxyl radical generated in a non-enzymatic system and found that ANPP can significantly scavenge free radical in a dose dependent manner than the standard catechin ( Figure 2 ). The radical scavenging activity of ANPP was found to be higher than the other extracts of this plant reported earlier [ 31 , 34 , 35 ]. Our result revealed that ANPP is a strong radical scavenger that may provide protection against free radicals induced by arsenic.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…We evaluated the ability of ANPP to scavenge hydroxyl radical generated in a non-enzymatic system and found that ANPP can significantly scavenge free radical in a dose dependent manner than the standard catechin ( Figure 2 ). The radical scavenging activity of ANPP was found to be higher than the other extracts of this plant reported earlier [ 31 , 34 , 35 ]. Our result revealed that ANPP is a strong radical scavenger that may provide protection against free radicals induced by arsenic.…”
Section: Discussioncontrasting
confidence: 64%
“…In this study we have been able to isolate a large content of polyphenols (phenolics and flavonoids) ANPP from the plant pods through extraction with methanol followed by chromatography with diaion resin ( Table 1 ). Interestingly, the content of flavonoids in ANPP was much higher than any other extracts reported earlier from this plant [ 31 , 34 , 35 ]. The presence of high content of polyphenolics suggests that ANPP might have potential antioxidant activity.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…7 A number of medicinal properties have acute diarrhoea. 8 The bark of plant is used extensively for colds, bronchitis, diarrhea, bleeding piles and leukoderma. 9 Pods and tender leaves are given to treat diarrhea and are also considered in folk medicine to treat diabetes mellitus.…”
mentioning
confidence: 99%